The Distinct Impact of Information and Incentives on Cheating - Julien Benistant; Fabio Galeotti; Marie Claire Villeval (Institute of Labor Economics (IZA), 2021)
We study a dynamic variant of the die-under-the-cup task where players can repeatedly misreport the outcomes of consecutive die rolls to earn more money, either under a non- competitive piece rate scheme or in a two-player competitive tournament. In this dynamic setting we test (i) whether giving continuous feedback (vs. final ex post feedback) on the opponent's reported outcome to both players encourages cheating behavior, and (ii) to what extent this influence depends on the incentive scheme in use (piece rate vs. tournament). We also vary whether the opponent is able to cheat or not. We find that people lie more when placed in a competitive rather than a non-competitive setting, but only if both players can cheat in the tournament. Continuous feedback on the counterpart's reports increases cheating under the piece-rate scheme but not in a competitive setting. Our results provide new insights on the role that feedback plays on cheating behavior in dynamic settings under different payment schemes, and shed light on the origins of the effect of competition on dishonesty.
Keywords: C92; M52; D83; 330; dishonesty; feedback; peer effects; competitive incentives; experiment